Sedulang Setudung Dance Learning using the Peer Tutor Method in Extracurricular Activities at SMK Unggul Negeri 2 Banyuasin Regency - Audian, Dwiky Dandy; Yelli, Nofroza; Ilhaq, Muhsin (CV. Rayyan Dwi Bharata, 2022)
TLearning Sedulang Setudung Dance Using the Peer Tutor Method in Extracurricular Activities at State Vocational High School 2 Banyuasin Regency. The formulation of the problem in this study is